1995
DOI: 10.1002/jnr.490400502
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin induces rise of free calcium in nuclei of neuroblastoma × glioma hybrid NG 108‐15 cells

Abstract: Confocal fluorescence microscopy was used to study the bradykinin-induced calcium signals in the neuroblastoma x glioma cell line NG 108-15. We found that bradykinin induced a rise in free calcium, not only in the cytoplasm but also in the nucleus. The nuclear and cytosolic calcium concentrations were not significantly different and rose to about 1.2 microM. The signal was mediated by the B2-receptor subtype as confirmed using the specific antagonist Hoe 140. Both the onset and the intensity of the calcium sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1995
1995
1997
1997

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
0
1
Order By: Relevance
“…These authors report that small changes of cytosolic Ca2+ caused rapid changes in nuclear Ca2+, whereas large cytosolic Ca2+ increases (above 300 nM) were found to be attenuated in the nucleus (Al-Mohanna et al, 1994). In a study on neuroblastoma x glioma hybrid cells, we found neither a gradient nor any attenuation (Beckmann et al, 1994b). Rather, the calcium signal rose to approximately 1.2 pM in both the nucleus and the cytosol.…”
Section: Activation Of Nuclear Pkccontrasting
confidence: 78%
“…These authors report that small changes of cytosolic Ca2+ caused rapid changes in nuclear Ca2+, whereas large cytosolic Ca2+ increases (above 300 nM) were found to be attenuated in the nucleus (Al-Mohanna et al, 1994). In a study on neuroblastoma x glioma hybrid cells, we found neither a gradient nor any attenuation (Beckmann et al, 1994b). Rather, the calcium signal rose to approximately 1.2 pM in both the nucleus and the cytosol.…”
Section: Activation Of Nuclear Pkccontrasting
confidence: 78%